MODIFICATION OF THE DUST COLLECTOR TOOL ON A 3 AXIS CNC ROUTER MACHINE FOR WOOD WORKING - Yahya, Ahmad; Koswara, Engkos; Rachmat, Asep; Dewi Jannati, Eidelweis (Universitas Majalengka, 2023)
Based on the results of research in Majalengka Regency, it was found that there were 200 semi-finished wood processing secondary industries, spread over 26 sub-districts with the type of wood used being dominated by teak, mahogany, these types of wood are used for semi-finished materials in the form of frames, doors, windows, cabinets, sideboard and chairs. There is also production of wood that is native to Indonesia, namely wood carving. Wood carving has its own uniqueness because it is a human creation based on an aesthetic sense according to what the human himself wants. Wood carving works of art are usually created using sculpting techniques. The creation of works of wood carving with the arrangement of elements so that meaningful elements are formed and one must have creative sculpting skills to produce works that are good, attractive and have meaning and high aesthetic value as well as being useful in people's lives.